ZnO as a conductive layer prepared by ALD for solar cells based on n-CdS/n-CdTe/p-Cu₁.₈S heterostructure - Semikina, T.V.; Mamykin, S.V.; Godlewski, M.; Luka, G.; Pietruszka, R.; Kopalko, K.; Krajewski, T.A.; Gierałtowska, S.; Wachnicki, L.; Shmyryeva, L.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
ZnO films with high conductivity are obtained by atomic layer deposition for application in solar cells based on n CdS/ n CdTe / p Cu₁.₈S heterostructure. The parameters of solar cells with ZnO electrode are calculated from light and dark currentvoltage characteristics and compared with those obtained for structures with Mo contact. The advantages of ZnO electrode are discussed.